Antioxidant Activity of Red Dragon Fruit Teabag (Hylocereus polyrhizus) Peels with the Addition of Ginger (Zingiber officinale var. amarum) and Cinnamon (Cinnamomum zeylanicum, BI) - Wima Anggitasari; Lindawati Setyaningrum; Muhammad Rofik Usman; Dyan Wigati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Free radicals have very unstable and reactive molecules. Excessive free radicals can trigger oxidative stress and cause various diseases. The peel of red dragon fruit contains chemical compounds that shows potential as an antioxidants. This study aims to optimize the benefits of red dragon fruit peels as tea bags because its convenient and simple to use. Design of this study was a randomized block design (RBD) which consisted of two factors, the drying temperature of the red dragon fruit skin (T) and the teabag formulation (F). Ginger and cinnamon are added as flavoring ingredients to the formula. The result showed that the drying temperature of the peel red dragon fruit affects the antioxidant activity of the teabag, where T1 has the highest antioxidant activity. The formulation of teabags also affects the antioxidant activity of the teabag, where F1 has the highest antioxidant activity. T1F1 had the highest antioxidant activity, and the interaction between the two (T and F) had a significant effect on antioxidant activity (p < 0.05).